A Randomized Controlled Trial of the eCHECKUP to GO for High School Seniors across the Academic Year. (10th November 2021) - Doumas, Diana M.; Esp, Susan; Turrisi, Rob; Bond, Laura
Abstract: Background: Among high school students, seniors report the highest levels of alcohol use and hazardous drinking. Technology-based interventions are a promising approach for reducing alcohol use among this age group. Objectives: This randomized controlled trial investigated the efficacy of the eCHECKUP TO GO, an online personalized feedback intervention, on reducing alcohol use among high school seniors across the academic year (ClinicalTrials.gov Identifier NCT03613818). Drinker risk status, with students classified as high- or low-risk drinkers based on baseline reports binge drinking, was examined as a moderator of intervention effects. Method: Participants ( N = 311) were recruited from two high schools. Class periods were randomized to the intervention condition or an assessment-only control condition. Participants completed online surveys at baseline, 30-day, and 6-month assessments. Results: Intervention effects were moderated by drinker risk status. Among high-risk drinkers, those in the intervention condition reported a significant reduction in weekly drinking quantity and estimated blood alcohol concentration (eBAC) at the 30-day follow-up relative to students in the control condition. By 6 months, reductions in alcohol outcomes among high-risk students in the intervention condition were sustained, but high-risk students in the control condition also reported reductions in weekly drinking. In contrast, for eBAC, intervention effects were significantly greater among students in the intervention condition relative to the control condition at 6 months. Conclusions: Results support the efficacy of the eCHECKUP TO GO for decreasing short-term alcohol use among seniors who are high-risk drinkers and provide preliminary evidence that reductions are sustained across the academic year.